Heart failure: a cardiovascular outcome in diabetes that can no longer be ignored. - McMurray, J; Gerstein, H; Holman, R; Pfeffer, M (Elsevier, 2014)
In patients with type 1 or type 2 diabetes, glycaemic exposure assessed as HbA1c correlates strongly with risk of future microvascular and macrovascular complications. Improved glucose control substantially reduces the risk of microvascular complications and, with extended follow-up, modestly reduces the risk of atherosclerotic events. The lowering of HbA1c concentrations by newly developed glucose-lowering drugs (alone or when added to other glucose-lowering drugs) has been used, until recently, as a surrogate measure of their potential to lower cardiovascular risk. This assumption is no longer acceptable, and now demonstration of cardiovascular safety has been mandated by regulatory authorities. A major concern, however, is the universal absence in any large-scale trials of new glucose-lowering drugs of hospital admission for heart failure as a prespecified component of the primary composite cardiovascular outcomes. This omission is important because hospital admission for heart failure is a common and prognostically important cardiovascular complication of diabetes. Moreover, it is the one cardiovascular outcome for which the risk has been shown unequivocally to be increased by some glucose-lowering therapies. As such, we believe that heart failure should be systematically evaluated in cardiovascular outcome trials of all new glucose-lowering drugs.